Diseño de la Estrategia de Formación al Talento Humano en Salud Sobre Drogodependencia - Rincón Rojas, Lina Paola (Universidad Antonio Nariño, 2024)
Health care for drug-dependent people poses challenges during its execution, such as stigmatization, limitation in access to services, among others. According to data from the United Nations, there has been an increase in the drug user population and with it needs for intervention, generating needs for the preparation of human talent in health, which provides care that responds to individual requirements and applying bioethical principles. The present work sought to design a training strategy for a group of human talent in health on drug dependence in an institution providing health services in the city of Ibagué